2019
DOI: 10.1371/journal.pone.0218580
|View full text |Cite
|
Sign up to set email alerts
|

Do changes in health reveal the possibility of undiagnosed pancreatic cancer? Development of a risk-prediction model based on healthcare claims data

Abstract: Background and objective Early detection methods for pancreatic cancer are lacking. We aimed to develop a prediction model for pancreatic cancer based on changes in health captured by healthcare claims data. Methods We conducted a case-control study on 29,646 Medicare-enrolled patients aged 68 years and above with pancreatic ductal adenocarcinoma (PDAC) reported to the Surveillance Epidemiology an End Results (SEER) tumor registries program in 2004–2011 and 88,938 age a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 31 publications
1
40
1
Order By: Relevance
“…Electronic health records (EHR) offer opportunities to utilize longitudinal and cumulative healthcare data to build prediction models. Parametric models that inform high-risk for PDAC among individuals with NOD or new-onset pre-diabetes have been developed, with varying predictive performances for PDAC [103][104][105][106] . A model of NOD patients residing in Minnesota, USA incorporated age at onset of DM, and changes in weight and blood glucose to identify persons at 4.5% 3-year predicted risk of PDAC with 78% sensitivity and 80% specificity (AUC = 0.87) 103 .…”
Section: Electronic Health Records-based Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Electronic health records (EHR) offer opportunities to utilize longitudinal and cumulative healthcare data to build prediction models. Parametric models that inform high-risk for PDAC among individuals with NOD or new-onset pre-diabetes have been developed, with varying predictive performances for PDAC [103][104][105][106] . A model of NOD patients residing in Minnesota, USA incorporated age at onset of DM, and changes in weight and blood glucose to identify persons at 4.5% 3-year predicted risk of PDAC with 78% sensitivity and 80% specificity (AUC = 0.87) 103 .…”
Section: Electronic Health Records-based Modelsmentioning
confidence: 99%
“…A Medicare claims-based model among individuals with NOD incorporating multiple health indicators including pancreatitis, dyspepsia, depression, abdominal pain, weight jaundice, nausea/vomiting has been applied to an elderly population with NOD. The model identifies persons at 3.5% predicted risk of PDAC over 1-year (AUC = 0.73) 106 . Insurance claims-based models with diagnoses, such as pancreatitis, dyspepsia, abdominal pain, weight loss, and jaundice, incorporating parametric 106 or machine-learning methods 107 have also been developed with limited diagnostic performance (AUC = 0.73).…”
Section: Electronic Health Records-based Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the included articles, four studies explained that LTDM is an independent risk factor for PC [5,7,8,9]. Seven studies showed that NOD precedes the onset of PC [9][10][11][12][18][19][20], and 13 studies proposed as to how NOD with certain clinical factors and screening tests can be used as a predictor for PC screening [1,7,12,14,16,18,19,[21][22][23][24][25][26][27]. Seven studies mentioned the relation between PC and DM after pancreatic surgery [28][29][30][31][32][33][34].…”
Section: Resultsmentioning
confidence: 99%
“…A prediction model of medicare enrollees provided some information about the risk factors that could be used to test for emergent diagnosis of PC. However, it was not applicable for population screening since they have excluded the data for three months before the development of PC [24]. All the above studies are to be validated further by conducting population-based prospective interventional studies to find out the best strategy.…”
Section: Screening Strategies For Early Diagnosis Of Pc In Patients Wmentioning
confidence: 99%